Applications of Thiol-Ene Chemistry for Peptide Science - Nolan, Mark D.; Scanlan, Eoin M. (Frontiers in Chemistry, 2020)
Radical thiol-ene chemistry has been demonstrated for a range of applications in peptide science, including macrocyclisation, glycosylation and lipidation amongst a myriad of others. The thiol-ene reaction offers a number of advantages in this area, primarily those characteristic of “click” reactions. This provides a chemical approach to peptide modification that is compatible with aqueous conditions with high orthogonality and functional group tolerance. Additionally, the use of a chemical approach for peptide modification affords homogeneous peptides, compared to heterogeneous mixtures often obtained through biological methods. In addition to peptide modification, thiol-ene chemistry has been applied in novel approaches to biological studies through synthesis of mimetics and use in development of probes. This review will cover the range of applications of the radical-mediated thiol-ene reaction in peptide and protein science.